The effect of consuming farmed salmon compared to salmon oil capsules on long chain omega 3 fatty acid and selenium status in humans : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Science in Human Nutrition, Institute of Food, Nutrition and Human Health at Massey University, Auckland, New Zealand - Pauga, Melanie (Massey University, 2009)
Salmon is a good source of long chain (LC) omega 3 fatty acids and selenium; these are well recognised for their health benefits. Recommendations for LC omega 3 fatty acid intakes presume equivalence between fish and fish oil. The aim of this research was to compare the effects of consuming salmon with salmon oil capsules on LC omega 3 fatty acid and selenium status. Forty four healthy subjects were randomly assigned to consume either two servings of 120 g farmed New Zealand King (FNZK) salmon/week or 2, 4 or 6 capsules of salmon oil/day for 8 weeks. Fasting blood samples, anthropometric measures, food consumption habits information and blood pressure (BP) measurements were obtained at the study commencement and ending. Each subject’s intake of LC omega 3 fatty acids and selenium was determined by analysing the fatty acid and selenium content of duplicate portions of cooked salmon and capsules. The amount of salmon consumed was then calculated by subtracting unconsumed amounts of salmon and then calculating the intake of LC omega 3 fatty acids as grams of LC omega 3 fatty acids consumed per day. Percentage of compliance to capsule intake, based on counts of unconsumed capsules, was calculated to determine the amount of LC omega 3 fatty acids consumed per day from capsules. Change in red blood cells (RBC) LC omega 3 fatty acid levels from equivalent amounts of LC omega 3 fatty acids consumed from capsules and salmon were compared using linear regression analysis predictive models fitted to the capsule data. Omega 3 index was calculated. LC omega 3 fatty acid intakes from salmon and 2, 4 and 6 capsules were 0.82, 0.24, 0.47 and 0.68 g/day, respectively. Equal amounts of LC omega 3 fatty acids consumed from salmon and capsules resulted in similar increases in RBC LC omega 3 fatty acids and omega 3 index (RBC eicosapentaenoic acid (EPA): 0.80 [0.58 – 1.02] vs. 1.00 [0.71 – 1.27] %; RBC docosahexaenoic acid (DHA): 0.93 [0.58 – 1.29] vs. 0.99 [0.68 – 1.31] %; omega 3 index: 1.92 [1.46 – 2.38] vs. 2.25 [1.65 – 2.83] %). The capsules did not contain selenium, but the salmon provided 6.84 µg selenium/day. Plasma selenium concentrations increased significantly in the salmon group compared to the capsule
Keywords: Human nutrition; Farmed salmon; Salmon oil; Omega 3 fatty acids; Selenium; Omega 3 index; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321205 Nutrition and dietetics